"The civil registration of indigenous peoples in the Cordillera region issues in implementing NSO administrative Order No. 3 of 2004 - Cruz, Gladys A. (Public Policy, 2016)
"Rules and Regulations Governing Registration of Acts and Events Concerning Civil Status of Indigenous Peoples" is the subject of National Statistics Office (NSO) Administrative Order (AO) No. 3 that was promulgated in 2004. After a decade or more of its existence, it is instructive for government and all concerned to identify and establish to what extent the intent of the Order "to respond to the expression of the ICCs/IPs for cultural integrity and to render basic services more responsive to the needs and desires of these communities" has been accomplished. This paper discusses the results of a study undertaken to assess the state of implementation of NSO AO No. 3 in the municipalities of the Cordillera Region for the period 2004 to 2012. Factors that facilitate as well as obstruct the offices of the loca civil registrar with the Orders provisions are discussed. Some recommendations are proposed to overcome these challenges in order that an effective registration system of civil events of members of IP communities can be put in place.